Trends in and correlates of CD4+ cell count at antiretroviral therapy initiation after changes in national ART guidelines in Rwanda. (2nd January 2015) - Mutimura, Eugene; Addison, Diane; Anastos, Kathryn; Hoover, Donald; Dusingize, Jean Claude; Karenzie, Ben; Izimukwiye, Isabelle; Mutesa, Leo; Nsanzimana, Sabin; Nash, Denis
Abstract : Background: Initiation of antiretroviral therapy (ART) in the advanced stages of HIV infection remains a major challenge in sub-Saharan Africa. This study was conducted to better understand barriers and enablers to timely ART initiation in Rwanda where ART coverage is high and national ART eligibility guidelines first expanded in 2007–2008. Methods: Using data on 6326 patients (≥15 years) at five Rwandan clinics, we assessed trends and correlates of CD4 + cell count at ART initiation and the proportion initiating ART with advanced HIV disease (CD4 + <200 cells/μl or WHO stage IV). Results: Out of 6326 patients, 4486 enrolling in HIV care initiated ART with median CD4 + cell count of 211 cells/μl [interquartile range: 131–300]. Median CD4 + cell counts at ART initiation increased from 183 cells/μl in 2007 to 293 cells/μl in 2011–2012, and the proportion with advanced HIV disease decreased from 66.2 to 29.4%. Factors associated with a higher odds of advanced HIV disease at ART initiation were male sex [adjusted odds ratios (AOR) = 1.7; 95% confidence interval (CI): 1.3–2.1] and older age (AOR46–55+ vs. <25 = 2.3; 95% CI: 1.2–4.3). Among those initiating ART more than 1 year after enrollment in care, those who had a gap in care of 12 or more months prior to ART initiation had higher odds of advanced HIV disease (AOR = 5.2; 95% CI: 1.2–21.1). Conclusion: Marked improvements in the median CD4 + cell count at ART initiation and proportion initiating ART with advanced HIV disease were observed following the expansion of ART eligibility criteria in Rwanda. However, sex disparities in late treatment initiation persisted through 2011–2012, and appeared to be driven by later diagnosis and/or delayed linkage to care among men.